GERMAN INSTITUTIONS IN VALPARAISO 1850 -1930: A FORM OF DEFENSE OF CULTURAL IDENTITY - Estrada Turra, Baldomero (Revista de Historia Social y de las Mentalidades, 2015)
It analyzes the different institutions created by  the German collectivity of Valparaiso, during  the period 1850-1930, in order to detect the  functions fulfilled regarding these organisms  stimulated German identity preservation or,  conversely, facilitated integration belonging  to the host society. Particularly striking is  the large number of institutions created  and the strong relationship between these  measures and the use of financial and trading  organizations of Germanic origin. On the other  hand, are perceived class features in many  of the associations, especially in the field of  sociability, thus meeting places are different. It  also receives a different level of participation  of the members of the community as a result  of the social position to which they belong, so  that the elite assumed the leadership and financial  support of associations and other sectors, they use  of the services delivered canceling those shares as  partners.
Keywords: German community; Associative; Identity; Sociability